Checklist das Cryptophyceae do estado de São Paulo, Brasil - Tucci, Andréa; Bicudo, Carlos Eduardo de Mattos; Menezes, Mariângela; Osti, João Alexandre Saviolo [UNESP]; Adame, Gisele (Instituto Virtual da Biodiversidade, 2011)
Usando como base de informações a monografia sobre o grupo publicada pelo projeto Flora Ficológica do Estado de São Paulo (Programa BIOTA), o acervo depositado no Herbário Científico do Estado de São Paulo Maria Eneyda P. Kauffmann Fidalgo (SP), a Lista de Espécies da Flora do Brasil e artigos científicos, dissertações e teses (com descrições e ilustrações) temos: nove gêneros e 39 espécies de criptoficeas, sendo 16 espécies exclusivas para o Estado de São Paulo, todas registradas em ambientes de água doce. A carência de especialistas no Estado de São Paulo e no Brasil, além de problemas de estratégia amostral, necessidade de uso da microscopia eletrônica e ausência de estudos de biologia molecular, são fatores que devem ter subestimado o conhecimento taxonômico de Cryptophyceae no Estado.

Based on the information provided by the monograph on the group published by the project Phycology Flora of São Paulo (BIOTA), the collection deposited in the Scientific Herbarium Mary P. Eneyda Kauffmann Fidalgoof the State of São Paulo, the List of Endangered Species of the Flora of Brazil and scientific papers, dissertations and theses (with descriptions and illustrations), there are nine genera and 39 species of cryptophytes, 16 of which are unique species to the State of São Paulo, all recorded in freshwater environments. The lack of specialists in the State of São Paulo and Brazil as well as problems in the sampling strategy, the necessary use of electronic microscopy and the absence of molecular biology studies are factors that must have underestimated the taxonomic knowledge of Cryptophyceae in the state.
Checklist of Cryptophyceae from São Paulo State, Brazil
Keywords: Cryptophyceae; Cryptomonas; biodiversidade; Programa BIOTA/FAPESP; Cryptophyceae; Cryptomonas; biodiversity; BIOTA/FAPESP Program